Monitoring the time-grade required for extrusion of oocytes reproductive from colossoma macropomum - Sevignani, D.; Buzzacaro, E.; Fortuna, N. B. (Scientific Electronic Archives, 2020)
The water temperature of the tanks of the breeding herds exerts a strong influence on the process of artificial reproduction. Its monitoring through the hour-degree, serves to assist in the moment to be made the extrusion of the oocytes. The objective was to monitor the time-degree that Colossoma macropomum females need after the second dose of the hormonal induction protocol, until the time of extrusion of their oocytes. The analysis was carried out at the Fish Fishery in the municipality of Sorriso-MT. Nine breeding women were submitted to the protocol of hormonal induction with pituitary extract of carp being administered in two doses. In the former, the dose of 0.5 mg / kg was used and the second dose was 5 mg / kg body weight, with an interval of 12 hours. From the second dose, the temperature in degrees centigrade of the water from the tanks was monitored hourly until the time of oocyte extrusion. Breeders had muscle tremors, swimming in circles, and were more agitated nine hours after the second dose. The oocytes had a yellowish-brown appearance, and some had individual features. The sum of the temperature of the water in hours-degree obtained was of 243. The temperature of the water did not present variation, maintaining itself at 27 Â° C. It is concluded that an hour-degree is necessary for an extrusion of oocytes in some of the things you can find in Colossoma Macropomum of 243, agreeing with the limits proposed in the literature.